Analysis Of Flavonoid Levels on Skin Langsat Fruit (Lansium Domesticum) Using Uv-Vis Spectrophotometer - Almarza, Almarza; Said, Irwan (Universitas Tadulako, 2023)
Langsat fruit (lansium domesticum) is a plant included in the family meliaceace. Several compounds were reported to have been isolated from multiple constituents in langsat plants that contain lansic acid, triterpene amino sugar glycoside, and dukunolides A- C, tetranortripenoid was dukunolides D- F. With the development of sciense a lot of research on ingredients and benefits langsat fruit both the pulp of the fruit and the skin. Empirically, the skin of the langsat fruit has been used as an anti-oxidant and anti-cancer treatment. Langsat fruit skin is an essential source of bioactive components such as phenols, flavonoids, tannins, saponins, triterpenoids, and alkaloids. This study used a UV-Vis spectrophotometer to determine the levels of flavonoids in the ethanol extract of langsat fruit peel (Lansium domesticum). This study aims to determine the levels of flavonoids in the skin of langsat fruit (lancium domesticum) by comparing the wet and dry fruit skin. Extraction of the chemical content of langsat fruit skin (Lansium domesticum) was carried out by the meseration method using ethanol 70.0/0. The determination of flavonoid levels in langsat fruit peel extract was measured at 520 nm and 700 nm from the result of the study. The total flavonoid levels of each sample were 2.856 mg /100 grams of alkaline fruit skin and 4.209mg /100 grams of dried langsat fruit peel. This shows that dried langsat fruit peel samples have high anti-oxidant power and alkaline fruit peel extracts.